HECT-Type E3 Ubiquitin Ligases in Cancer. Issue 12 (December 2019) - Bernassola, Francesca; Chillemi, Giovanni; Melino, Gerry
Abstract : Ubiquitination, a post-translational modification that involves a covalent attachment of ubiquitin to a protein substrate, is essential for cellular homeostatic maintenance. At the end of a three-enzyme cascade, E3 ubiquitin ligases (E3s) recruit substrates and promote or directly catalyze ubiquitin transfer to targets. These enzymes largely determine the specificity of the ubiquitination reaction. Genetic alteration, abnormal expression, or dysfunction of E3s account for the occurrence and progression of human cancers. Indeed, excessive degradation of relevant tumor-suppressor molecules and impaired disposal of oncogenic proteins have been linked to tumorigenesis. This review focuses on the emerging roles of HECT-type E3s in tumorigenesis, and emphasizes how perturbations of these enzymes contribute to cancer pathogenesis. Highlights: The HECT-type E3 ubiquitin ligases constitute a small subfamily of E3s (28 enzymes in human) that have intrinsic enzymatic activity. Members of the subfamily of HECT-type E3s are frequently deregulated in human cancers. Aberrant expression, mutations, and deregulated activity of the HECT enzymes have been associated with cancer development and chemoresistance. HECT-type E3s contribute to tumorigenesis by regulating the ubiquitination levels of substrates that act as either tumor suppressors or oncogenes. Some HECT E3s behave as pro- or antioncogenic factors depending on the cellular context, substrate selectivity, and binding of adaptor proteins that may facilitate the recruitment of specific targets.